Validation of Analytical Methods of Several Secondary Metabolic Compounds in Andrographis paniculata, Zingiber officinale var. rubrum, and Nigella sativa as COVID-19 Therapy: A Review - Farendina Suarantika; Nabila Hadiah Akbar (Jurnal Ilmiah Medicamento, 2022)
Several Indonesian plants contain active compounds that can limit infection and replication of SAR-CoV-2 based on their activity against relevant therapeutic targets. This literature review aims to review validated analytical methods on bitter plants (Andrographis paniculata), red ginger (Zingiber officinale var. rubrum), and black cumin (Nigella sativa), which has potential therapeutic activity against SARS-CoV-2. Sources of information used in this literature review were obtained using search engines such as Science Direct, Google Scholar, and PubMed. Andrographolide (sambiloto), gingerol (red ginger), and thymoquinone (black cumin) were shown to be specifically capable of inactivating SARS-CoV-2 with good targeting accuracy. The generally validated plant analysis methods used RP-HPLC/HPTLC, UV-Vis Spectrophotometry, GC-FID, GC, and UHPLC-DAD.